SORPTION OF EU(III)/CM(III) ON CA-MONTMORILLONITE AND NA-ILLITE. PART 1: BATCH SORPTION AND TIME-RESOLVED LASER FLUORESCENCE SPECTROSCOPY EXPERIMENTS - Rabung Th.; Pierret M.C.; Bauer A.; Geckeis H.; Bradbury M.H.; Baeyens B. (My University, 2005)
Sorption of Cm(III) and Eu(III) at trace concentrations onto Ca-montmorillonite (SWy-1) and Na-illite (Illite du Puy) has been studied under anaerobic conditions by batch sorption experiments and time-resolved laser fluorescence spectroscopy (TRLFS). Comparison of the results from spectroscopic and batch sorption experiments with Cm and Eu indicates the existence of outer-sphere complexes at pH <4 in the experiments with Na-illite (0.25 g/L solid; 2.5 × 10−7 mol/L Cm; 0.1 mol/L NaClO4). In the case of Ca-montmorillonite, (0.25 g/L solid, 2.5 × 10−7 mol/L Cm or 10−6 mol/L Eu, 0.066 mol/L Ca(ClO4)2), Cm/Eu outer-sphere complexes do not form at significant levels due to the Ca2+ competition for the clay mineral cation-exchange sites. TRLFS spectra indicate the formation of inner-sphere surface complexes at pH >5 for both clay minerals. Five H2O/OH− molecules remain in the first metal ion coordination sphere of the sorbed Eu/Cm. Measured fluorescence lifetimes of sorbed Eu/Cm and peak deconvolution of Cm-spectra are consistent with the formation of surface complexes of the form ≡S-O-Eu/Cm(OH)x(2−x)(H2O)5−x. At pH ≥ 12 Cm becomes incorporated into a surface precipitate at the Ca-montmorillonite surface presumably composed of Ca(OH)2 or calcium silicate hydrate. A dramatic shift of the fluorescence emission band by more than 20 nm and a clear increase in the fluorescence lifetime suggests the almost complete displacement of coordinated H2O and OH−. The pH dependent Eu sorption data obtained in batch experiments are consistent with spectroscopic data on Eu and Cm within experimental uncertainties thus demonstrating the validity of Eu as a homologue for trivalent actinides. Parameterization of a two-site protolysis nonelectrostatic surface complexation and cation exchange model using the batch sorption data and spectroscopic results is discussed in Part 2 of this work.